tert-Butyl 2-borono-1H-pyrrole-1-carboxylate - Zhong, Zheng (International Union of Crystallography, 2009)
In the crystal structure of the title compound, C(9)H(14)BNO(4), the boronic acid group and carbamate groups are nearly co-planar with the pyrrole ring, making dihedral angles of 0.1 (2) and 2.2 (2)°, respectively. Intramolecular and intermolecular O—H⋯O hydrogen bonds help to stabilize the structure, the latter interaction leading to inversion dimers..